Experience of weekly cisplatin concurrent with intensity-modulated radiotherapy for locally advanced nasopharyngeal carcinoma patients with resistance to neoadjuvant chemotherapy. Issue 44 (November 2017) - Chen, Chuanben; Chen, Taojun; Huang, Chaoxiong; Wang, Jing; Fei, Zhaodong
Abstract : Abstract: Nasopharyngeal carcinoma (NPC) is highly sensitive to radiotherapy. Locally advanced NPC has a relatively poor prognosis if treated with radiotherapy alone. Several studies have demonstrated that chemoradiotherapy confers survival benefit in locally advanced NPC. However, a small proportion of patients are resistant to chemotherapy based on cisplatin. So, it is important to make a valuable and inexpensive schedule for these patients. After 2 cycles of neoadjuvant chemotherapy that consisted of gemcitabine and cisplatin (80 mg/m 2, every 3 weeks) or paclitaxel and cisplatin (80 mg/m 2, every 3 weeks), magnetic resonance imaging (MRI) was used to evaluate efficacy. A total of 13 patients with extensive nodal disease or/and bulky tumors volume were determined with a stable disease (SD) and enrolled in this study. Cisplatin at a dose of 30 mg/m 2 administered weekly concurrent with intensity-modulated radiotherapy (IMRT) was used to treat these patients resistant to neoadjuvant chemotherapy. The efficacy was evaluated by tumor response and the change of tumor volume. After the completion of concurrent chemoradiotherapy (CCRT), the overall tumor response was a complete response (CR) for 4 of 13 (30.8%) patients and partial response (PR) for 9 of 13 (69.2%) patients. The mean primary tumor volume was reduced by 59.7% and 89.8% at the 24th fraction of IMRT and after the completion of IMRT, respectively. The mean nodal volume was reduced by 63.8% and 93.5% at the 24th fraction of IMRT and after completion of IMRT, respectively. The study showed that weekly cisplatin concurrent with IMRT improved the treatment parameters for locally advanced NPC with resistance to neoadjuvant chemotherapy based on cisplatin. It was a valuable and relatively inexpensive schedule to improve the prognosis for these patients.